A transparent invasion: a first Mediterranean record and an established population of the glassfish Ambassis dussumieri Cuvier 1828 - STERN, NIR; GAYER, KFIR; MOROV, ARSENIY (Mediterranean Marine Science, 2022)
In this study, we document the first record of the glassfish Ambassis dussumieri in the Mediterranean Sea. Confirmation for taxonomic identity has been conducted using morphological and molecular approaches and was based on a sub-sample of six individuals that were collected from a large school that resides within an artificial protected bay of a local power plant in Tel Aviv, Israel. This unique occurrence of an undisturbed school of invasive species is hereby discussed.